Redd+ in a climate of injustice - McBreen, James Patrick (2013)
This research attempts to elucidate the beneficial role of the REDD+ mechanism in the mitigation of climate change, as well as justice-related issues to its implementation. It examines equity issues involved in climate change and carbon trading through the REDD+ mechanism. Addressing its shortcomings without entering into deeper debates about the legitimacy of the market system in which most of us operate. A key assumption of this research is that the impending expiration of the Kyoto Protocol is bound with the expectation that any new international agreement on actions for addressing global climate change will include the development of REDD+ programmes.